Interdependent happiness across age in Costa Rica, Japan, and the Netherlands. Issue 4 (23rd October 2020) - Hitokoto, Hidefumi; Takahashi, Yoshiaki
Abstract : Age‐related patterns of interdependent happiness were compared across general adult samples from Costa Rica, Japan, and the Netherlands using surveys. Interdependent happiness is the individual perception of one's degree of interpersonal harmony, quiescence, and ordinariness. Based on the available evidence concerning age‐related changes in well‐being, the authors predicted and found that interdependent happiness is positively correlated with age in Costa Rica and Japan, but not in the Netherlands. The cultural meaning of happiness and its life‐long nourishment are discussed.